The Influence of Zig-Zag Exercise on Shooting Accuracy in Soccer Games for Class V of SD Negeri Tasa XI Lais, Musi Banyuasin - Yulaili, Yulaili; Rosani, Meilia; Putri, Siti Ayu Risma (Journal of Social Work and Science Education, 2023)
The purpose of this study was to determine the effect of zig-zag training on shooting accuracy in a soccer game for children of class V SD Negeri Tasa XI, Lais District. This research was conducted at SD Negeri Tasa XI, Lais District, which is located Tj. Agung Utara, Kec. Lais, Musi Banyuasin Regency, South Sumatra 30757. The method used in this research is the pre-experimental design experimental method. The research design used in this study was a pre-test and post-test one group design. The population of this study was all of class V at SD Negeri Tasa XI, Lais District, with a total of 26 people. The sample in this study is the existing population or is called a saturated sample (census) of 26 people. Data collection was carried out by conducting shooting tests in soccer games. The analytical method used is the t test with SPSS for windows version 23.00. The results of this study are that there is an effect of zig-zag training on shooting accuracy in soccer games for children of class V SD Negeri Tasa XI, Lais District.